Characterization of the Desiccation Tolerance of Cronobacter sakazakii Strains - Du, Xin-jun; Wang, Xiao-yi; Dong, Xuan; Li, Ping; Wang, Shuo (Frontiers in Microbiology, 2018)
Strong desiccation tolerance is an outstanding feature of Cronobacter sakazakii and can enable the bacterium to survive in a dry food matrix (such as milk powder) for a long time. Therefore, contamination of food possessing low water activity with C. sakazakii can increase the risk of infection in human beings, particularly in neonates and infants. However, the mechanism underlying the desiccation tolerance property of C. sakazakii is largely unknown. In this study, the desiccation tolerance characteristics of 42 C. sakazakii strains were analyzed. Simultaneously, the sequence types and biofilm formation abilities of the strains were investigated, and their correlations with desiccation tolerance were analyzed. The results showed no significant correlation between desiccation tolerance and sequence type. However, there was a positive correlation between biofilm formation ability and desiccation tolerance. Raman spectroscopy was employed to investigate the biofilm formed by strains with distinct desiccation tolerance levels, and the results showed that the levels of polysaccharide, proteins and carotenoid might play important roles in the resistance to dry environments. In addition, 10 genes involved in osmoprotectant synthesis or transport were selected, and their differential expression in strains with diverse desiccation tolerance levels was compared to investigate whether these genes were responsible for cytoprotection in the dry environment. The results revealed a great difference in gene expression among strains with different desiccation tolerance levels, suggesting that these genes play a regulatory role in the resistance of C. sakazakii to dry environments. Our study provides a useful reference for follow-up studies investigating the mechanism of desiccation tolerance in C. sakazakii.